Reconstructive Surgery for Head and Neck Cancer Patients - Hanasono, Matthew M. (Adv Med, 2014)
The field of head and neck surgery has gone through numerous changes in the past two decades. Microvascular free flap reconstructions largely replaced other techniques. More importantly, there has been a paradigm shift toward seeking not only to achieve reliable wound closure to protect vital structures, but also to reestablish normal function and appearance. The present paper will present an algorithmic approach to head and neck reconstruction of various subsites, using an evidence-based approach wherever possible.